Psycholinguistic functions in war poetry: a comparative study of the battles of Uhud and Maldon - Nurul Iman Mohamad Anuar Kamal,; Suziana Mat Saad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
War poetry functions not only as an aesthetic form but also as a psychological medium that processes trauma, reinforces identity, and motivates communities. Yet, research on classical Arabic and Old English war poetry has focused primarily on historical and rhetorical aspects, with limited attention to psycholinguistic dimensions. This gap restricts a deeper understanding of how poetic language operates as a psychological instrument for coping with war trauma across cultural traditions. This study aims (i) to analyse the emotional, cognitive, and therapeutic dimensions of Kaʿb ibn Mālik's poetry on the Battle of Uhud (625 CE) and the anonymous Old English poem The Battle of Maldon (991 CE); (ii) to compare their linguistic strategies; and (iii) to evaluate how poetic discourse shapes collective identity and resilience. A qualitative comparative textual analysis was employed. The findings reveal five dominant themes: trauma and grief, heroism and courage, loyalty and solidarity, collective motivation, and spiritual or feudal honour. Despite differing cultural contexts, both texts transform defeat into resilience through repetition, metaphor, rhythm, and parallelism. Ultimately, this research illuminates how poetic language—ancient or modern—functions as linguistic therapy for communities facing conflict, reaffirming its enduring relevance to both cultural and psychological resilience.